Aspendos, Türkei: Die Arbeiten der Jahre 2012 bis 2014 - Bachmann, Martin (e-Forschungsberichte des DAI, 2023)
Aspendos is one of the most important urban centers of Roman Asia Minor, but was neglected in archaeological research for longtime. Well known are the impressive and virtuous drawings of major Roman monuments by George Niemann from the late 19th century. In 2008 a multi-annual survey project was started by Veli Köse (Ankara Hacettepe Üniversitesi) in Aspendos, with the aim to create a uniform level of documentation and a detailed knowledge base for an excavation project carried out for the first time in Aspendos. The first excavation campaign was started in 2012 in cooperation with the Museum of Antalya. The Istanbul Department of the German Archaeological Institute is involved in this research project of Veli Köse in cooperation and carried out primarily architectural surveys of the major Roman monuments, but was also involved in the excavation documentation.